A discussion on the outcomes of adopted agricultural technological products and specific sustainable development goals: Evidence from Pakistan - Muhammad Bilal; Bernhard Brümmer; Jan Barkmann (Cogent Economics & Finance, 2022)
Establishing a link between specific sustainable development goals (SDGs) and the outcomes of adopted agricultural technological products is lacking in developing countries. Therefore, this study aims to address food security SDG 02 by adopting crop protection products of multinational brands versus sub-standard crop protection products SDG 12 by smallholder farming households. We employ endogenous switching probit models using a survey of smallholder farming households in the cotton-wheat zone in Pakistan. Full information maximum likelihood estimates illustrate that comparative advantage guide the adoption of crop protection products of multinational brands (CMBs). Our findings suggest that adopting CMBs rather than sub-standard crop protection products may translate as a responsible farming practice if assuming the use of crop protection products is inevitable. In sum, CMBs enhance food security and can play a vital role in the current debate on responsible consumption and production, particularly for sustainable development. Our findings also indicate that promoting agricultural extension information via radio broadcasts has a significant and positive relationship with adoption. Hence, it stands out as the most promising policy option.
Keywords: 330; adoption; agricultural extension; food security; smallholders; socio-demographic